Synthesis of 3-aryl-2-phosphinoimidazo[1, 2-a]pyridine ligands for use in palladium-catalyzed cross-coupling reactions. Issue 31 (5th June 2019) - Tran, Ryan Q.; Jacoby, Seth A.; Roberts, Kaitlyn E.; Swann, William A.; Harris, Nekoda W.; Dinh, Long P.; Denison, Emily L.; Yet, Larry
Abstract : 3-Aryl-2-phosphoimidazo[1, 2- a ]pyridine ligands were prepared via two complimentary synthetic routes and were evaluated in the Suzuki–Miyaura and Buchwald–Hartwig amination cross-coupling reactions. Abstract : 3-Aryl-2-phosphinoimidazo[1, 2- a ]pyridine ligands were synthesized from 2-aminopyridine via two complementary routes. The first synthetic route involves the copper-catalyzed iodine-mediated cyclizations of 2-aminopyridine with arylacetylenes followed by palladium-catalyzed cross-coupling reactions with phosphines. The second synthetic route requires the preparation of 2, 3-diiodoimidazo[1, 2- a ]pyridine or 2-iodo-3-bromoimidazo[1, 2- a ]pyridine from 2-aminopyridine followed by palladium-catalyzed Suzuki/phosphination or a phosphination/Suzuki cross-coupling reactions sequence, respectively. Preliminary model studies on the Suzuki synthesis of sterically-hindered biaryl and Buchwald–Hartwig amination compounds are presented with these ligands.